Pembinaan Prestasi di Pusat Pendidikan dan Latihan Olahraga Pelajar (PPLP) Provinsi Jawa Tengah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study is to find out about the stages of development, the process recruitment of athletes and coaches, organizations, funding management, training programs and infrastructure as the main factor in the implementation of fostering achievement in PPLP Central Java Province. The research approach used qualitative descriptive approach. The results of this study are 1) each sports has performed stages good development , 2) The process of recruiting athletes and coaches has gone through the correct procedures but there are some athletes that have been set, 3) each sport has a training program made periodically and made by coaches, 4) The management of the Central Java PPLP organization has been arranged neatly and structurally, 5) the support of these facilities and infrastructure is still less and not even available for some sports so it inhibits training process. It can be concluded that achievement development is conducted in PPLP Central Java has been going well, but there are some factors that inhibit the development process on athlete achievement.